PERAN KANTOR URUSAN AGAMA DALAM PENCEGAHAN PERNIKAHAN DI BAWAH UMUR: ANALISIS YURIDIS TERHADAP UNDANG-UNDANG NOMOR 16 TAHUN 2019 TENTANG PERKAWINAN DAN KOMPILASI HUKUM ISLAM - Khoirul Anam; Jamiliya Susantin (Jurnal Yustitia, 2026)
Underage marriage remains a serious problem in Indonesia, negatively affecting reproductive health, education, and child welfare. This study aims to examine the role of the Office of Religious Affairs (KUA) in preventing underage marriage based on Law Number 16 of 2019 concerning Marriage and the Compilation of Islamic Law (KHI), and to juridically analyze KUA’s authority and preventive efforts. The research employs a normative legal method using statute and conceptual approaches. Primary legal materials include Law Number 16 of 2019, Presidential Instruction Number 1 of 1991 on KHI, and Ministerial Regulation Number 20 of 2019 on Marriage Registration. The findings indicate that Indonesian marriage regulations set the minimum marriage age at 19 years for both men and women, granting KUA the authority to verify marriage requirements, check the age of prospective spouses, and refuse registration of marriages that do not comply with legal provisions. Beyond administrative functions, KUA also plays a strategic preventive role through marriage counseling, socialization of minimum marriage age, legal education, and empowerment of Islamic Religious Extension Workers. From an Islamic legal perspective, this role falls under the category of Maslahah bi As-Saddu Dzariah, an effort to prevent harm by closing pathways to wrongdoing. Nevertheless, the effectiveness of KUA’s role highly depends on synergy among KUA, families, communities, and related institutions. Optimization of KUA’s preventive functions must be continuously strengthened to protect children’s rights and promote family welfare in accordance with Islamic and Indonesian positive law. Keywords: Office of Religious Affairs, Underage Marriage, Law Number 16 of 2019, Compilation of Islamic Law, Prevention